FAUNA OF THE SIBERIAN EPITHELIAL DUCT - DR.RIADIA MURPHY, DR.RIADIA MURPHY; PONGUS, DR. KAZAMANT (International Journal of Multidisciplinary Research and Studies, 2021)
A helminthological study of six adult Siberian deer (Capreolus pygargus) individuals from Primorsky Krai was performed. The abomasa and tiny intestine contents were assessed. All animals were infected with nematodes, and also the intensity of infection ranged from tens to many specimens. Spiculopteragia spiculoptera was the dominant species, and Mazamastrongylus dagestanica and Nematodirus filicollis were also detected. Ostertagia antipini and a minor morph of S. spiculoptera, “Rinadia mathevossiani”, were observed for the primary time in Primorsky Krai. Besides, the Spirurida nematode Pygarginema skrjabini was detected in one roe, and also the trematode Dicrocoelium dendriticum was found within the small intestines of two roes.